DEEP NEURAL NETWORKS FOR SKIN LESIONS DIAGNOSTICS - Michalska-Ciekańska, Magdalena (Informatyka, Automatyka, Pomiary w Gospodarce i Ochronie Środowiska, 2022)
Non-invasive diagnosis of skin cancer is extremely necessary. In recent years, deep neural networks and transfer learning have been very popular in the diagnosis of skin diseases. The article contains selected basics of deep neural networks, their interesting applications created in recent years, allowing the classification of skin lesions from available dermatoscopic images.